Tackling chronic illnesses by regulating intake of unhealthy foods in India: A viewpoint - Sudip Bhattacharya; Sheikh Mohd Saleem; Om Prakash Bera (Wolters Kluwer Medknow Publications, 2022)
Chronic illnesses linked to diet, such as cardiovascular disease, cancer, and diabetes, have become a serious concern for the current health-care system. Approximately 39.5 million people worldwide died of noncommunicable diseases (NCDs) in 2016, including 17.6 million from cardiovascular disease and 8.9 million from cancer. Over the past decade, worldwide mortality rates for cardiovascular diseases and cancer have increased by 14.5% and 17.8%, respectively. In France, cardiovascular disease and cancer are the leading causes of death, accounting for more than 30% of all deaths. Chronic illnesses are associated with poor nutritional quality in many countries. Considering the high burden of chronic diseases linked to poor diet, health-care authorities have adopted community-based public health strategies to improve diet and to minimize the risk of nutrition-related disorders. Front-of-pack nutrition labels (FoPLs) are gaining popularity in this arena. FoPLs aim to guide customers toward healthier choices by delivering simple, salient, and readily accessible nutritional information about food products at the time of purchase. It will be wise if we introduce FoPL by empowering public to make their informed choice during purchasing packaged food items. We hope in the future, food industry will make food policy in similar lines with healthy public health policy to prevent the future burden of NCD in India and the globe.